2017
DOI: 10.1002/ange.201704849
|View full text |Cite
|
Sign up to set email alerts
|

Native Desorption Electrospray Ionization Liberates Soluble and Membrane Protein Complexes from Surfaces

Abstract: Mass spectrometry (MS) applications for intact protein complexes typically require electrospray( ES) ionization and have not been achieved via direct desorption from surfaces.D esorption ES ionization (DESI) MS has however transformed the study of tissue surfaces through release and characterisation of small molecules.Motivated by the desire to screen for ligand binding to intact protein complexes we report the development of an ative DESI platform. By establishing conditions that preserve non-covalent interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…Noncovalent complexes between the ligand biotin and proteins avidin, bovine serum albumin, and haemoglobin were detected as shown in Figure B. Similar studies have recently been described for native DESI analysis of purified samples of intact proteins and protein assemblies; Ambrose et al describe detection of monomeric proteins such as apo lysozyme and bovine serum albumin, complexes of tetrameric alcohol dehydrogenase and tetradecameric GroEL using ammonium acetate solutions . They also show that native DESI is suitable for the analysis of membrane proteins, although some detergent sensitivity is exhibited, and for probing noncovalent protein interactions in the example of NAG‐5 bound to lysozyme.…”
Section: Native Lesa Mssupporting
confidence: 71%
See 1 more Smart Citation
“…Noncovalent complexes between the ligand biotin and proteins avidin, bovine serum albumin, and haemoglobin were detected as shown in Figure B. Similar studies have recently been described for native DESI analysis of purified samples of intact proteins and protein assemblies; Ambrose et al describe detection of monomeric proteins such as apo lysozyme and bovine serum albumin, complexes of tetrameric alcohol dehydrogenase and tetradecameric GroEL using ammonium acetate solutions . They also show that native DESI is suitable for the analysis of membrane proteins, although some detergent sensitivity is exhibited, and for probing noncovalent protein interactions in the example of NAG‐5 bound to lysozyme.…”
Section: Native Lesa Mssupporting
confidence: 71%
“…Progress has since been made to mitigate these effects by use of solvent additives . In another approach, by modifying the DESI set‐up itself, DESI mass spectra of native protein complexes of up to 800 kDa in size (tetradecameric GroEL) spotted onto glass slides have recently been recorded . An alternative approach for analysing the surface layer of liquid samples generated ions of protein complexes of approximately 150 kDa .…”
Section: Ambient Surface Sampling Mass Spectrometry Techniquesmentioning
confidence: 99%
“…However, LILBID is still an infusion‐based technique and – similar to MALDI – produces mostly singly and doubly charged ions [10] . Desorption electrospray ionisation (DESI) has been successfully applied to non‐covalent protein complexes by the group of Robinson, demonstrating desorption of spray‐deposited protein complexes from a surface [11] . Additionally, liquid extraction surface analysis (LESA), a nano‐ESI based surface sampling method has also been shown to be compatible with native‐MS [12]…”
Section: Figurementioning
confidence: 99%
“…[10] Desorption electrospray ionisation (DESI) has been successfully applied to noncovalent protein complexes by the group of Robinson, demonstrating desorption of spray-deposited protein complexes from a surface. [11] Additionally, liquid extraction surface analysis (LESA), a nano-ESI based surface sampling method has also been shown to be compatible with native-MS. [12] Shiea et al [13] and others [14] demonstrated laser ablation electrospray ionisation (LAESI)-based analysis of various small proteins, such as myoglobin, cytochrome C and hemoglobin sub-units. These results were obtained with traditional electrospray solvents and additives, containing a high organic modifier percentage and high acidity.…”
mentioning
confidence: 99%
“…The analysis of proteins and their complexes is an important endeavor as nearly all biological processes involve regulated interactions between proteins and other biomolecules (e.g., DNA, RNA, cofactors, and other proteins) in both time and space . Because of its incomparable sensitivity, speed, and specificity, electrospray ionization mass spectrometry (ESI-MS) has emerged as an ideal tool for protein analysis. The last two decades have seen the rapid development in an area of gas-phase structural biology, which aims to leverage the advantages of MS analysis for elucidation of a three-dimensional protein structure with the combination of ion mobility, fragmentation, and spectroscopy. Thus, it is of foundational significance to determine the extent of the native structure of a protein retained after desolvation. It is now well-established that the nativelike compact conformer of a protein can be maintained after desolvation made evident by the relatively low charge states of a gaseous protein produced from nondenaturing aqueous solution by ESI. A recent study that combined ESI-MS with ion mobility measurements and soft landing techniques and further made convincing the survival of the overall compactness of many proteins when desolvated. …”
mentioning
confidence: 99%